Understanding the Bible: Biblical hermeneutics in modern perspective - MacRae, Allan A.; Peri, Ronald J.; Grauley, John E.; Harding, William N.; Dunzweiler, Robert J.; Vannoy, J. Robert; Newman, Robert C.; Varner, Will; Taylor, Thomas V. (Bible Evangelism, 1979)
Biblical inerrancy / A. MacRae -- Thematic interpretation / R. Peri -- Cultic interpretation / J. Grauley -- Interpretation of difficult passages / W. Harding -- Time in predictive prophecy / R. Dunzweiler -- Archaeology and interpretation / R. Vannoy -- Interpreting the miraculous / R. Newman -- Interpretation of prophetic Scriptures / W. Varner -- Interpreting the parables / R. Newman -- Options in hermeneutics / T. Taylor.